The labor market in Finland, 2000-2016 - Tomi Kyyrä; Hanna Pesola (IZA World of Labor, 2018)
Finland's population is aging rapidly by international comparison. The shrinking working-age population means that the burden of increasing pension and health care expenditures is placed on a smaller group of employed workers, while the scope for economic growth through increased labor input diminishes. Fiscal sustainability of the welfare state calls for a high employment rate among people of working age. Recent increases in employment among older groups contribute favorably to public finances, but high overall unemployment and a large share of the long-term unemployed are serious concerns.
Keywords: E24; J3; 330; real earnings; unemployment; Finland